Differences in the recruitment properties of the corticospinal pathway between the biceps femoris and rectus femoris muscles - Higashihara, Ayako; Nakagawa, Kento; Futatsubashi, Genki; Sekiguchi, Hirofumi; Nagano, Yasuharu; Hirose, Norikazu (Brain research, 2022)
[Display omitted] •This is the first study to report the recruitment properties of BFlh and RF muscles.•A sigmoidal relationship was observed between the stimulus intensity and MEP amplitude.•Compared to RF, BFlh had a lower plateau, maximum slope, and threshold.•The recruitment properties of the corticospinal pathway differ between BFlh and RF. The neuromuscular activity in the hamstring and quadriceps muscles is vital for rapid force control during athletic movements. This study aimed to investigate the recruitment properties of the corticospinal pathway of the biceps femoris long head (BFlh) and rectus femoris (RF) muscles. Thirty-two male subjects were participated in this study. Corticospinal excitability was investigated for BFlh and RF during the isometric knee flexion and extension tasks, respectively, using transcranial magnetic stimulation. A sigmoidal relationship was observed between the stimulus intensity and amplitude of motor-evoked potentials and characterized by a plateau value, maximum slope, and threshold. Compared with RF, BFlh had a significantly lower plateau value (P < 0.001, d = 1.17), maximum slope (P < 0.001, r = 0.79), and threshold (P = 0.003, d = 0.62). The results showed that the recruitment properties of the corticospinal pathway significantly differ between BFlh and RF. These results reveal that when a sudden large force is required during athletic movements, the RF can produce force through a rapid increase in the recruitment of motor units. The BFlh, on the other hand, requires larger or more synchronized motor commands for enabling the proper motor unit behavior to exert large forces. These differences in the neurophysiological factors between the hamstrings and quadriceps can have a substantial effect on the balance of force generation during athletic activities.